Conditions of Confinement in Juvenile Detention and Correctional Facilities: (United States), 1991 ([Verlag nicht ermittelbar], 1996)
This study was conducted for the Office of Juvenile Justice and Delinquency Prevention (OJJDP) to (1) collect and analyze data on conditions of confinement in public and private juvenile facilities, (2) determine the extent to which conditions were consistent with those required by nationally recognized standards for juvenile confinement facilities, (3) suggest explanations for variations in conformance to standards among facilities, and (4) assist OJJDP in formulating recommendations for improving conditions of confinement. In challenging the premise that high levels of conformance to nationally recognized standards result in improved conditions of confinement, this study examined client outcomes. Areas of concern for juvenile facilities usually center on living space, health care, security, and control of suicidal behavior. Key incident measures provided in this data collection include injuries, escapes, acts of suicidal behavior, incidents requiring emergency health care, and isolation incidents. Part 1, Mail Survey Data, collected information from facility administrators. Part 2, Site Visit Data, consists of questions answered by the juvenile inmates as well as by the independent observers who administered the on-site surveys. Additional variables in Part 2 that are not present in Part 1 include subjective measures such as the quality of the food, medical care, and recreation facilities, and whether various facility programs were effective. The study covered all 984 public and private juvenile detention centers, reception centers, training schools, and ranches, camps, and farms in the United States. Three types of facilities were excluded: (1) youth halfway houses, shelters, and group homes, (2) police lockups, adult jails, and prisons that held juveniles tried and convicted as adults, and (3) psychiatric and drug treatment programs.